The modified Kansei Engineering-based application for sustainable service design - Hartono, Markus (International journal of industrial ergonomics, 2020)
Considering the human-centered design, this paper shows a modified-integrated approach of how to quantify the impact of perceived Kano's attractive services on perceived emotional satisfaction (Kansei), followed by the formulation of innovative ideas for sustainable services using TRIZ (known as Theory of Inventive Problem Solving). The Kano's attractive service attribute is deemed to be a significant emotional booster (known as Kansei). Kansei Engineering (KE) is used to highlight the level of customer emotional satisfaction due to perceived service offerings. For the past seven years, there has been a rapid concern in Kansei Engineering (KE) in services. However, previous research of KE has mainly focused on the improvement and analysis of general service domains. There is little attention to sustainable services. Hence, this study provides a modified KE-based approach and aims to understand and satisfy customer emotional needs (Kansei) considering the social, environmental and economic performance. An empirical study in an international airport lounge and lobby services was conducted to confirm the applicability of the proposed model. Purposive sampling through in-depth-interview and face-to-face questionnaires which involved 100 valid subjects was used. Theoretically, these studies show the importance of Kansei's role in sustainable service development, highlighting more innovative and breakthrough solutions with less contradiction and “true-meaning” of Kansei. Practically, it provides a guideline for service designer and manager in identifying which attractive-based service attributes need to be prioritized considering Kansei satisfaction. •A modified integrative Kansei Engineering-based approach incorporating Kano's performance categories and TRIZ (Theory of Inventive Problem Solving) principles.•Customer Kansei satisfaction considering sustainability dimensions (social, environmental and economic performance).•Confirmatory mechanism for “true meaning” of Kansei linear model as a function of perceived service attributes .•Kansei role in sustainable service development provides more innovative and breakthrough solutions with less contradiction and “true-meaning” of Kansei.•A practical guideline for service providers in prioritizing the critical service attributes with regard to Kansei satisfaction.